Tanggung Jawab Notaris dalam Penyusunan Akta Otentik Terkait Terjadinya Tindak Pidana Pemalsuan Tanda Tangan oleh Notaris - Annisa Rahmaini; Edi Tarsono; Endra Wijaya (CV Rewang Rencang, 2025)
Notaries must ensure that all Acte they draw up fully comply with legal provisions, reflect the wishes of the parties, and are based on the facts of the case. As a public official, Notaries are not permitted to exceed the authority granted to them by law, and are prohibited from signing or certifying authentic Acte without the presence of the parties or without verifying their identities and signatures. However, the reality on the ground shows that there have been deviations from these provisions. In this case, the Notary did not thoroughly verify the presence of the parties or the authenticity of the signatures contained in the Acte. In fact, the Notary was known to have signed the Acte without ensuring the direct presence of the parties at the time of signing. This action not only contradicts the principle of prudence, but also causes the Acte in question to be legally flawed and lose its authenticity. The act of drafting and signing a power of attorney to sell without the presence of the interested parties, as well as using a forged signature, constitutes a violation of Section 264(1) of the Criminal Code in conjunction with Section 55(1)(1) of the Criminal Code, as well as Section 1365 of the Civil Code. Furthermore, violations of the provisions of the Notary Profession Law and the Notary Code of Ethics also indicate serious deviations in the performance of duties. The Panel of Judges has imposed a prison sentence, but dismissal as a notary without honor still requires a separate administrative process.